2022
DOI: 10.1002/glia.24290
|View full text |Cite
|
Sign up to set email alerts
|

Focused ion beam‐scanning electron microscopy links pathological myelin outfoldings to axonal changes in mice lacking Plp1 or Mag

Abstract: Healthy myelin sheaths consist of multiple compacted membrane layers closely encasing the underlying axon. The ultrastructure of CNS myelin requires specialized structural myelin proteins, including the transmembrane-tetraspan proteolipid protein (PLP) and the Ig-CAM myelin-associated glycoprotein (MAG). To better understand their functional relevance, we asked to what extent the axon/myelinunits display similar morphological changes if PLP or MAG are lacking. We thus used focused ion beam-scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Equally reasonable, these features may resolve in NAWM as swelled myelinated axons may recover by adjusting their myelin thickness, explaining the unaltered g-ratio. This may overcome disrupted axonal conduction and preserve axonal shape by limiting further swelling as recently proposed [ 56 ]. This implies that the thickness of pre-existing myelin is not static and that mature oligodendrocytes are able to re-instate myelin membrane expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Equally reasonable, these features may resolve in NAWM as swelled myelinated axons may recover by adjusting their myelin thickness, explaining the unaltered g-ratio. This may overcome disrupted axonal conduction and preserve axonal shape by limiting further swelling as recently proposed [ 56 ]. This implies that the thickness of pre-existing myelin is not static and that mature oligodendrocytes are able to re-instate myelin membrane expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted November 22, 2022. ; https://doi.org/10. 1101/2022.11.21.517320 doi: bioRxiv preprint al., 2018Gutiérrez et al, 1995), (2) the progressive axonopathy that is caused by energy deficits and is likely preceded by conduction blocks in fiber tracts that appear morphologically intact (Trevisiol et al, 2021), (3) the secondary gliosis, as also documented for Cnp KO mice (Garcia-Agudo et al, 2019;Janova et al, 2018), another mutant with structural abnormalities of myelin (Lappe-Siefke et al, 2003;Snaidero et al, 2017), or (4) any combination hereof.…”
Section: Discussionmentioning
confidence: 99%
“…Plp1 null myelin has been extensively studied in the past and subtle ultrastructural abnormalities have been described (Klugmann et al, 1997; Möbius et al, 2016; Patzig et al, 2016; Rosenbluth et al, 2006, Steyer et al, 2022). We have shown that PLP, which provides structural stability to compact myelin, also stabilizes the architecture of the ‘myelinic channel system’ (Steyer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations